Sodium-nickel mixed ion battery and preparation method thereof

By using materials such as Ni powder and conductive carbon nanotubes in sodium ion batteries, and using sodium-nickel mixed ion electrolyte, the side reactions and dendrite problems of existing sodium ion batteries during cyclic charging and discharge are solved, and the battery performance with high safety, high capacity and long life is achieved.

CN119764532APending Publication Date: 2025-04-04HUBEI ENG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411704086.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing sodium ion batteries are prone to side reactions and uncontrollable metal dendrites during cyclic charging and discharging, resulting in safety hazards and sudden drop in capacity.

Method used

Ni powder is used as the active material for the negative electrode, combined with conductive carbon nanotubes and PTFE, and a negative electrode sheet is made by roll pressing, sodium nickel mixed ion electrolyte is used, and sodium vanadium phosphate is used as the positive electrode material.

Benefits of technology

No dendrites are generated during cyclic charging and discharging, which improves the safety of the battery and has high capacity, long life and high rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764532A_ABST
    Figure CN119764532A_ABST
Patent Text Reader

Abstract

The invention provides a sodium-nickel mixed ion battery and a preparation method thereof, and belongs to the technical field of secondary batteries. The Ni powder is used as the active material of the sodium-nickel mixed ion battery negative electrode, the sodium-nickel mixed ion solution is used as the electrolyte, and the sodium vanadium phosphate positive electrode material is used as the active material of the sodium-nickel mixed ion battery positive electrode, so that the prepared sodium-nickel mixed ion battery does not generate dendritic crystals in the cyclic charging and discharging process, and has relatively high safety; the material has high charge-discharge specific capacity and excellent cycle performance, and solves the problems of potential safety hazards, sudden capacity drop and the like caused by side reaction and uncontrollable metal dendrites of a rechargeable sodium metal battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a sodium-nickel mixed ion battery and a preparation method thereof. Background Art

[0002] As a powerful alternative to lithium-ion batteries (LIBs), sodium-ion batteries (SIBs) are gradually gaining attention due to their advantages in sustainability and cost-effectiveness. Sodium resources are abundant and low-cost, making it particularly suitable for large-scale energy storage applications. The manufacturing process of SIBs is similar to that of LIBs, including mixing, coating, drying, cutting and other steps. Among the many sodium-ion battery cathode materials, sodium vanadium phosphate (Na3V2(PO4)3, NVP) has been widely studied due to its excellent electrochemical and structural properties, including high theoretical capacity (117 mA h / g), stable voltage platform (~3.4 V), long life and three-dimensional structure suitable for sodium ion migration.

[0003] In the prior art, sodium foil is usually used as the negative electrode of rechargeable sodium metal batteries (RSMBs) to evaluate the sodium ion storage performance of NVP positive electrodes. However, RSMBs often encounter complex side reactions and uncontrollable metal dendrites, leading to safety hazards and sudden capacity drop. Therefore, it is urgent to develop a sodium ion battery with excellent electrochemical performance and high safety performance. Summary of the invention

[0004] In view of the above deficiencies in the prior art, the present invention provides a sodium-nickel hybrid ion battery and a preparation method thereof. The novel sodium-based hybrid ion battery constructed by the present invention has the advantages of high capacity and high cycle stability.

[0005] To achieve the above purpose, the specific technical solutions of the present invention are as follows:

[0006] A sodium-nickel mixed ion battery comprises a positive electrode, a negative electrode and an electrolyte;

[0007] The negative electrode comprises Ni powder;

[0008] The electrolyte is a sodium-nickel mixed ion electrolyte; the sodium-nickel mixed ion electrolyte is obtained by uniformly mixing sodium trifluoromethanesulfonate, nickel trifluoromethanesulfonate and an ether solvent.

[0009] The sodium-nickel mixed ion battery provided by the present invention adopts Ni powder as the negative electrode, and no dendrites are generated during the cyclic charge and discharge process, thereby improving the safety of the battery; compared with the pure nickel ion battery in the prior art, the sodium-nickel mixed ion battery of the present invention has the advantages of high rate performance and long life; in addition, the present invention adopts Ni powder, conductive carbon nanotubes and PTFE to make the negative electrode plate by rolling, thereby reducing the use of nickel metal, and does not contain a corrosion inhibitor harmful to human health, and will not pose a threat to human health; the use of the negative electrode Ni powder is compared with the nickel plate, and the high specific surface area of ​​the nickel powder increases the surface chemical activity of the nickel, thereby accelerating the Ni 2+ / The reaction rate of Ni is improved by adjusting the ratio between Ni powder, conductive carbon nanotubes and PTFE, thereby improving the charge and discharge rate of sodium-nickel hybrid ion batteries.

[0010] Furthermore, the molar ratio of sodium trifluoromethanesulfonate to nickel trifluoromethanesulfonate is (0.1-2): (0.1-2).

[0011] Furthermore, the ether solvent is a mixture of one or more of ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (DEGDME), and tetraethylene glycol dimethyl ether (TEGDME).

[0012] Furthermore, the negative electrode also includes conductive carbon nanotubes and polytetrafluoroethylene (PTFE).

[0013] Furthermore, the mass ratio of the Ni powder (x), the conductive carbon nanotubes (y), and the PTFE is x:y:(100-xy); wherein, 40≤x≤80, 10≤y≤50, and x+y≤90.

[0014] Furthermore, the positive electrode comprises sodium vanadium phosphate positive electrode material.

[0015] The method for preparing the sodium-nickel mixed ion battery comprises the following steps:

[0016] (1) Mix sodium vanadium phosphate positive electrode material, conductive carbon nanotubes, and polyvinylidene fluoride (PVDF), add a small amount of N-methylpyrrolidone, grind evenly, and apply it on the positive electrode current collector. The surface density is controlled to be 2~3 mg / cm 2 , drying to obtain a positive electrode sheet;

[0017] (2) Ni powder, conductive carbon nanotubes and polytetrafluoroethylene are mixed, and a solvent is added to grind the mixture to obtain a uniform mixture; the uniform mixture is pressed into a sheet with a thickness of 15 to 25 mm, and dried to obtain a negative electrode sheet;

[0018] (3) uniformly mixing sodium trifluoromethanesulfonate, nickel trifluoromethanesulfonate and an ether solvent to obtain a sodium-nickel mixed ion electrolyte;

[0019] (4) Place the positive electrode sheet, glass fiber membrane, and negative electrode sheet in order, add sodium-nickel mixed ion electrolyte dropwise until the positive electrode sheet and glass fiber membrane are moistened, and seal to obtain a sodium-nickel mixed ion battery.

[0020] Furthermore, the mass ratio of the sodium vanadium phosphate positive electrode material, the conductive carbon nanotubes, and polyvinylidene fluoride is 80:10:10.

[0021] Furthermore, the positive electrode current collector is one of aluminum foil, carbon-coated aluminum foil, titanium foil and stainless steel foil.

[0022] Furthermore, in the sodium-nickel mixed ion electrolyte, the concentration of sodium trifluoromethanesulfonate is 0.1-2 mol / L.

[0023] Furthermore, in the sodium-nickel mixed ion electrolyte, the concentration of nickel trifluoromethanesulfonate is 0.1-2 mol / L.

[0024] Compared with the prior art, the present invention is beneficial in that:

[0025] (1) The present invention uses Ni powder as the active material of the negative electrode and a solution of sodium-nickel mixed ions as the electrolyte. The prepared sodium-nickel mixed ion battery has the advantages of high capacity and good cycle performance. Compared with sodium metal batteries, the sodium-nickel mixed ion battery using Ni powder as the active material of the negative electrode does not generate dendrites during the cyclic charge and discharge process, thereby improving the safety of the battery. Compared with simple nickel-ion batteries, the sodium-nickel mixed ion battery has the advantages of high rate and long life.

[0026] (2) Compared with the nickel-ion battery in the prior art, the negative electrode of the sodium-nickel-ion battery hybrid ion battery provided by the present invention is a pole piece after Ni powder, conductive carbon and PTFE are rolled, which reduces the use of nickel metal and does not contain corrosion inhibitors that are harmful to human health, and is safer.

[0027] (3) The sodium-nickel mixed ion battery provided by the present invention has excellent electrochemical performance, high safety performance, simple assembly process, low cost, and is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 CV curve of the sodium-nickel hybrid ion battery in Example 1 at a scan rate of 0.1 mV / S;

[0029] Figure 2 The battery cycle performance diagram of the sodium-nickel hybrid ion battery in Example 1 at a current density of 2C;

[0030] Figure 3 The battery cycle performance diagram of the sodium-nickel mixed ion battery in Comparative Example 1 at a current density of 2C;

[0031] Figure 4 The battery cycle performance diagram of the sodium-nickel mixed ion battery at 2C current density in Comparative Example 2;

[0032] Figure 5 This is a battery cycle performance diagram of the sodium-nickel mixed ion battery in Comparative Example 3 at a current density of 2C. DETAILED DESCRIPTION

[0033] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The present invention provides a sodium-nickel mixed ion battery, comprising a positive electrode, a negative electrode and an electrolyte;

[0035] The negative electrode comprises Ni powder;

[0036] The electrolyte is a sodium-nickel mixed ion electrolyte; the sodium-nickel mixed ion electrolyte is obtained by uniformly mixing sodium trifluoromethanesulfonate, nickel trifluoromethanesulfonate and an ether solvent.

[0037] In some examples, the molar ratio of sodium trifluoromethanesulfonate to nickel trifluoromethanesulfonate is (0.1-2): (0.1-2).

[0038] In some examples, the ether solvent is a mixture of one or more of ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (DEGDME), and tetraethylene glycol dimethyl ether (TEGDME).

[0039] The negative electrode further includes conductive carbon nanotubes and polytetrafluoroethylene (PTFE).

[0040] In some examples, the mass ratio of the Ni powder (x), the conductive carbon nanotubes (y), and the PTFE is x:y:(100-xy); wherein 40≤x≤80, 10≤y≤50, and x+y≤90.

[0041] The positive electrode includes a sodium vanadium phosphate positive electrode material; the sodium vanadium phosphate positive electrode material can be prepared using existing technology or directly purchased; in the following specific embodiments, the sodium vanadium phosphate positive electrode material is directly purchased.

[0042] Example 1

[0043] A sodium-nickel mixed ion battery, the preparation method is as follows:

[0044] S1. Mix sodium vanadium phosphate positive electrode material, conductive carbon nanotubes, and PVDF in a mass ratio of 80:10:10, add a small amount of N-methylpyrrolidone, grind evenly, and apply it on the positive electrode current collector. The surface density is controlled to 2 mg / cm 2 , dried in an oven at 105°C for 24 h, and cut into electrodes with a diameter of 10 mm for later use;

[0045] S2. Grind Ni powder, conductive carbon nanotubes and PTFE in isopropanol in a mass ratio of 60:20:20 to obtain a uniform mixture; place the uniform mixture in a roller press and repeatedly roll-press the mixture to a thickness of 22 mm. After the pressed sheet is placed in an oven at 105 °C for 24 h, it is cut into electrodes with a diameter of 15 mm for later use;

[0046] S3, mixing sodium trifluoromethanesulfonate, nickel trifluoromethanesulfonate and DEGDME uniformly to obtain a sodium-nickel mixed ion electrolyte containing 1 mol / L sodium trifluoromethanesulfonate and 1 mol / L nickel trifluoromethanesulfonate;

[0047] S4. Assemble 2025 button-type sodium-nickel hybrid ion batteries, place the positive electrode sheet, glass fiber membrane, and negative electrode sheet in order, add electrolyte until the positive electrode sheet and glass fiber membrane are wetted, seal the battery, and test the electrochemical performance after leaving it for 24 hours. The results are shown in Figure 1~2 And Table 1.

[0048] Figure 1 This is a CV curve diagram of the sodium-nickel hybrid ion battery of Example 1 at a scan rate of 0.1 mV / S. It can be seen from the curve that the sodium-nickel hybrid ion battery has a group of oxidation / reduction peaks in the voltage range of 0.01-1.3V, and after 20 cycles, the CV curve consistency remains good, indicating that the sodium-nickel hybrid ion battery of the present invention has excellent electrochemical reversibility and cycle stability.

[0049] Figure 2 The battery cycle performance diagram of the sodium-nickel mixed ion battery of Example 1 at a current density of 2C shows that its maximum discharge specific capacity can reach 95.8 mA h / g; after 1500 cycles, its capacity retention rate can reach 65.7%. This result shows that the sodium-nickel mixed ion battery of the present invention has the advantages of high capacity and long life.

[0050] Example 2

[0051] A sodium-nickel mixed ion battery, the preparation method is as follows:

[0052] S1. Mix sodium vanadium phosphate positive electrode material, conductive carbon nanotubes, and PVDF in a mass ratio of 80:10:10, add a small amount of N-methylpyrrolidone, grind evenly, and apply it on the positive electrode current collector. The surface density is controlled to 2 mg / cm2 , dried in an oven at 105°C for 24 h, and cut into electrodes with a diameter of 10 mm for later use;

[0053] S2. Grind Ni powder, conductive carbon nanotubes and PTFE in isopropanol in a mass ratio of 70:20:10 to obtain a uniform mixture; place the uniform mixture in a roller press and repeatedly roll-press the mixture to a thickness of 22 mm. After the pressed sheet is placed in an oven at 105 °C for 24 h, it is cut into electrodes with a diameter of 15 mm for later use;

[0054] S3, mixing sodium trifluoromethanesulfonate, nickel trifluoromethanesulfonate and DME uniformly to obtain a sodium-nickel mixed ion electrolyte containing 0.5 mol / L sodium trifluoromethanesulfonate and 0.5 mol / L nickel trifluoromethanesulfonate;

[0055] S4. Assemble 2025 button-type sodium-nickel hybrid ion batteries, place the positive electrode sheet, glass fiber membrane, and negative electrode sheet in order, add electrolyte until the positive electrode sheet and glass fiber membrane are moistened, seal the battery, and test the electrochemical performance after leaving it for 24 hours. The results are shown in Table 1.

[0056] Example 3

[0057] A sodium-nickel mixed ion battery, the preparation method is as follows:

[0058] S1. Mix sodium vanadium phosphate positive electrode material, conductive carbon nanotubes, and PVDF in a mass ratio of 80:10:10, add a small amount of N-methylpyrrolidone, grind evenly, and apply it on the positive electrode current collector. The surface density is controlled to 2 mg / cm 2 , dried in an oven at 105°C for 24 h, and cut into electrodes with a diameter of 10 mm for later use;

[0059] S2. Grind Ni powder, conductive carbon nanotubes and PTFE in isopropanol in a mass ratio of 50:35:15 to obtain a uniform mixture; place the uniform mixture in a roller press and repeatedly roll-press the sheet to a thickness of 22 mm; dry the sheet in an oven at 105 °C for 24 h, and cut it into 15 mm diameter pole pieces for later use;

[0060] S3, mixing sodium trifluoromethanesulfonate, nickel trifluoromethanesulfonate and TEGDME uniformly to obtain a sodium-nickel mixed ion electrolyte containing 1 mol / L sodium trifluoromethanesulfonate and 0.75 mol / L nickel trifluoromethanesulfonate;

[0061] S4. Assemble 2025 button-type sodium-nickel hybrid ion batteries, place the positive electrode sheet, glass fiber membrane, and negative electrode sheet in order, add electrolyte until the positive electrode sheet and glass fiber membrane are moistened, seal the battery, and test the electrochemical performance after leaving it for 24 hours. The results are shown in Table 1.

[0062] Example 4

[0063] A sodium-nickel mixed ion battery, the preparation method is as follows:

[0064] S1. Mix sodium vanadium phosphate positive electrode material, conductive carbon nanotubes, and PVDF in a mass ratio of 80:10:10, add a small amount of N-methylpyrrolidone, grind evenly, and apply it on the positive electrode current collector. The surface density is controlled to 2 mg / cm 2 , dried in an oven at 105°C for 24 h, and cut into electrodes with a diameter of 10 mm for later use;

[0065] S2. Grind Ni powder, conductive carbon nanotubes and PTFE in isopropanol in a mass ratio of 60:25:15 to obtain a uniform mixture; place the uniform mixture in a roller press and repeatedly roll-press the sheet to a thickness of 22 mm; dry the sheet in an oven at 105 °C for 24 h, and cut it into 15 mm diameter pole pieces for later use;

[0066] S3, mixing sodium trifluoromethanesulfonate, nickel trifluoromethanesulfonate and DME uniformly to obtain a sodium-nickel mixed ion electrolyte containing 0.5 mol / L sodium trifluoromethanesulfonate and 2 mol / L nickel trifluoromethanesulfonate;

[0067] S4. Assemble 2025 button-type sodium-nickel hybrid ion batteries, place the positive electrode sheet, glass fiber membrane, and negative electrode sheet in order, add electrolyte until the positive electrode sheet and glass fiber membrane are moistened, seal the battery, and test the electrochemical performance after leaving it for 24 hours. The results are shown in Table 1.

[0068] Example 5

[0069] A sodium-nickel mixed ion battery, the preparation method is as follows:

[0070] S1. Mix sodium vanadium phosphate positive electrode material, conductive carbon nanotubes, and PVDF in a mass ratio of 80:10:10, add a small amount of N-methylpyrrolidone, grind evenly, and apply it on the positive electrode current collector. The surface density is controlled to 2 mg / cm 2 , dried in an oven at 105°C for 24 h, and cut into electrodes with a diameter of 10 mm for later use;

[0071] S2. Grind Ni powder, conductive carbon nanotubes and PTFE in isopropanol in a mass ratio of 70:10:20 to obtain a uniform mixture; place the uniform mixture in a roller press and repeatedly roll-press the mixture to a thickness of 22 mm. After the pressed sheet is placed in an oven at 105 °C for 24 h, it is cut into electrodes with a diameter of 15 mm for later use;

[0072] S3, mixing sodium trifluoromethanesulfonate, nickel trifluoromethanesulfonate and TEGDME uniformly to obtain a sodium-nickel mixed ion electrolyte containing 1 mol / L sodium trifluoromethanesulfonate and 0.25 mol / L nickel trifluoromethanesulfonate;

[0073] S4. Assemble 2025 button-type sodium-nickel hybrid ion batteries, place the positive electrode sheet, glass fiber membrane, and negative electrode sheet in order, add electrolyte until the positive electrode sheet and glass fiber membrane are moistened, seal the battery, and test the electrochemical performance after leaving it for 24 hours. The results are shown in Table 1.

[0074] Example 6

[0075] A sodium-nickel mixed ion battery, the preparation method is as follows:

[0076] S1. Mix sodium vanadium phosphate positive electrode material, conductive carbon nanotubes, and PVDF in a mass ratio of 80:10:10, add a small amount of N-methylpyrrolidone, grind evenly, and apply it on the positive electrode current collector. The surface density is controlled to 2 mg / cm 2 , dried in an oven at 105°C for 24 h, and cut into electrodes with a diameter of 10 mm for later use;

[0077] S2. Grind Ni powder, conductive carbon nanotubes and PTFE in isopropanol in a mass ratio of 50:25:25 to obtain a uniform mixture; place the uniform mixture in a roller press and repeatedly roll-press the mixture to a thickness of 22 mm. After the pressed sheet is placed in an oven at 105 °C for 24 h, it is cut into electrodes with a diameter of 15 mm for later use;

[0078] S3, mixing sodium trifluoromethanesulfonate, nickel trifluoromethanesulfonate and DEGDME uniformly to obtain a sodium-nickel mixed ion electrolyte containing 1 mol / L sodium trifluoromethanesulfonate and 1 mol / L nickel trifluoromethanesulfonate;

[0079] S4. Assemble 2025 button-type sodium-nickel hybrid ion batteries, place the positive electrode sheet, glass fiber membrane, and negative electrode sheet in order, add electrolyte until the positive electrode sheet and glass fiber membrane are moistened, seal the battery, and test the electrochemical performance after leaving it for 24 hours. The results are shown in Table 1.

[0080] Comparative Example 1

[0081] A sodium-nickel mixed ion battery, the preparation method is as follows:

[0082] S1. Mix sodium vanadium phosphate positive electrode material, conductive carbon nanotubes, and PVDF in a mass ratio of 80:10:10, add a small amount of N-methylpyrrolidone, grind evenly, and apply it on the positive electrode current collector. The surface density is controlled to 2 mg / cm 2, dried in an oven at 105°C for 24 h, and cut into electrodes with a diameter of 10 mm for later use;

[0083] S2. Grind Ni powder, conductive carbon nanotubes and PTFE in isopropanol in a mass ratio of 60:20:20 to obtain a uniform mixture; place the uniform mixture in a roller press and repeatedly roll-press the mixture to a thickness of 22 mm. After the pressed sheet is placed in an oven at 105 °C for 24 h, it is cut into electrodes with a diameter of 15 mm for later use;

[0084] S3, mixing sodium trifluoromethanesulfonate and DEGDME uniformly to obtain an electrolyte containing 1 mol / L sodium trifluoromethanesulfonate;

[0085] S4. Assemble 2025 button-type sodium-nickel hybrid ion batteries, place the positive electrode sheet, glass fiber membrane, and negative electrode sheet in order, add electrolyte until the positive electrode sheet and glass fiber membrane are wetted, seal the battery, and test the electrochemical performance after leaving it for 24 hours. The results are shown in Figure 3 And Table 1. Figure 3 It shows that at a current density of 2C, the battery has a maximum discharge capacity of 52.7 mA h / g, and after 500 cycles, its capacity retention rate is only 4.3 mA h / g.

[0086] Comparative Example 2

[0087] A sodium-nickel mixed ion battery, the preparation method is as follows:

[0088] S1. Mix sodium vanadium phosphate positive electrode material, conductive carbon nanotubes, and PVDF in a mass ratio of 80:10:10, add a small amount of N-methylpyrrolidone, grind evenly, and apply it on the positive electrode current collector. The surface density is controlled to 2 mg / cm 2 , dried in an oven at 105°C for 24 h, and cut into electrodes with a diameter of 10 mm for later use;

[0089] S2. Grind Ni powder, conductive carbon nanotubes and PTFE in isopropanol in a mass ratio of 70:20:10 to obtain a uniform mixture; place the uniform mixture in a roller press and repeatedly roll-press the mixture to a thickness of 22 mm. After the pressed sheet is placed in an oven at 105 °C for 24 h, it is cut into electrodes with a diameter of 15 mm for later use;

[0090] S3, uniformly mixing nickel trifluoromethanesulfonate and DME to obtain an electrolyte containing 1 mol / L nickel trifluoromethanesulfonate;

[0091] S4. Assemble 2025 button-type sodium-nickel hybrid ion batteries, place the positive electrode sheet, glass fiber membrane, and negative electrode sheet in order, add electrolyte until the positive electrode sheet and glass fiber membrane are wetted, seal the battery, and test the electrochemical performance after leaving it for 24 hours. The results are shown in Figure 4 And Table 1. Figure 4 It shows that at a current density of 2C, the battery has a maximum discharge capacity of 16.5 mA h / g, and after 500 cycles, its capacity retention rate is only 5.8 mA h / g.

[0092] Comparative Example 3

[0093] A sodium-nickel mixed ion battery, the preparation method is as follows:

[0094] S1. Mix sodium vanadium phosphate positive electrode material, conductive carbon nanotubes, and PVDF in a mass ratio of 80:10:10, add a small amount of N-methylpyrrolidone, grind evenly, and apply it on the positive electrode current collector. The surface density is controlled to 2 mg / cm 2 , dried in an oven at 105°C for 24 h, and cut into electrodes with a diameter of 10 mm for later use;

[0095] S2, cutting the Ni sheet with a thickness of 0.1 mm into a diameter of 15 mm for later use;

[0096] S3, mixing sodium trifluoromethanesulfonate, nickel trifluoromethanesulfonate and TEGDME uniformly to obtain a sodium-nickel mixed ion electrolyte containing 1 mol / L sodium trifluoromethanesulfonate and 0.75 mol / L nickel trifluoromethanesulfonate;

[0097] S4. Assemble 2025 button-type sodium-nickel hybrid ion batteries, place the positive electrode sheet, glass fiber membrane, and negative electrode sheet in order, add electrolyte until the positive electrode sheet and glass fiber membrane are wetted, seal the battery, and test the electrochemical performance after leaving it for 24 hours. The results are shown in Figure 5 And Table 1. Figure 5 It shows that at a current density of 2C, the battery has a maximum discharge capacity of 32.8 mA h / g. After 100 cycles, its capacity retention rate is only 3.2 mA h / g.

[0098] Table 1: Performance test results of the batteries prepared in Examples 1 to 6 and Comparative Examples 1 to 3 at 2C current density

[0099]

[0100] It can be seen from Table 1 that the sodium-nickel mixed ion battery prepared by the present invention has a higher discharge specific capacity, and after 1500 cycles, its capacity retention rate is higher than 60%; while the sodium ion battery prepared by using only sodium trifluoromethanesulfonate solution as the electrolyte (Comparative Example 1), or only using nickel trifluoromethanesulfonate solution as the electrolyte (Comparative Example 2), or using nickel sheet as the negative electrode sheet (Comparative Example 3) has a lower discharge specific capacity and poor cycle performance.

[0101] In summary, the present invention uses Ni powder as the active material of the negative electrode of the sodium-nickel mixed ion battery, uses a sodium-nickel mixed ion solution as the electrolyte, and uses a sodium vanadium phosphate positive electrode material as the active material of the positive electrode of the sodium-nickel mixed ion battery. The prepared sodium-nickel mixed ion battery does not generate dendrites during the cyclic charge and discharge process, has high safety, high charge and discharge specific capacity and excellent cycle performance, and solves the safety hazards and capacity drop caused by side reactions and uncontrollable metal dendrites in rechargeable sodium metal batteries.

[0102] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.

Claims

1. A sodium-nickel mixed ion battery, comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The negative electrode includes Ni powder; the electrolyte is a sodium-nickel mixed ion electrolyte; the sodium-nickel mixed ion electrolyte is obtained by uniformly mixing sodium trifluoromethanesulfonate, nickel trifluoromethanesulfonate and a solvent.

2. A sodium-nickel hybrid ion battery according to claim 1, characterized in that: The molar ratio of the sodium trifluoromethanesulfonate to the nickel trifluoromethanesulfonate is (0.1-2): (0.1-2).

3. A sodium-nickel hybrid ion battery according to claim 1, characterized in that: The negative electrode also includes conductive carbon nanotubes and polytetrafluoroethylene.

4. A sodium-nickel mixed ion battery according to claim 3, characterized in that: The mass ratio of the Ni powder, the conductive carbon nanotubes and the polytetrafluoroethylene is x:y:(100-xy); wherein, 40≤x≤80, 10≤y≤50, and x+y≤90.

5. A sodium-nickel hybrid ion battery according to claim 1, characterized in that: The positive electrode includes sodium vanadium phosphate positive electrode material.

6. The method for preparing a sodium-nickel mixed ion battery according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) After mixing sodium vanadium phosphate positive electrode material, conductive carbon nanotubes and polyvinylidene fluoride, adding a small amount of N-methylpyrrolidone, grinding evenly, coating on the positive electrode current collector, and drying to obtain a positive electrode sheet; (2) mixing Ni powder, conductive carbon nanotubes and polytetrafluoroethylene, adding a solvent and grinding to obtain a uniform mixture; pressing the uniform mixture into sheets, drying it and obtaining a negative electrode sheet; (3) uniformly mixing sodium trifluoromethanesulfonate, nickel trifluoromethanesulfonate and a solvent to obtain a sodium-nickel mixed ion electrolyte; (4) Place the positive electrode sheet, glass fiber membrane, and negative electrode sheet in order, add sodium-nickel mixed ion electrolyte until the positive electrode sheet and glass fiber membrane are moistened, and seal to obtain a sodium-nickel mixed ion battery.

7. The method for preparing a sodium-nickel mixed ion battery according to claim 6, characterized in that: The mass ratio of the sodium vanadium phosphate positive electrode material, the conductive carbon nanotubes and polyvinylidene fluoride is 80:10:

10.

8. The method for preparing a sodium-nickel mixed ion battery according to claim 6, characterized in that: In the sodium-nickel mixed ion electrolyte, the concentration of sodium trifluoromethanesulfonate is 0.1-2 mol / L.

9. The method for preparing a sodium-nickel mixed ion battery according to claim 6, characterized in that: In the sodium-nickel mixed ion electrolyte, the concentration of nickel trifluoromethanesulfonate is 0.1-2 mol / L.